The gift of the crocodile : a Cinderella story - Sierra, Judy (Simon & Schuster Books for Young Readers, 2000)
In this Indonesian version of the Cinderella story, a girl named Damura escapes her cruel stepmother and stepsister and marries a handsome prince with the help of Grandmother Crocodile.